2023
DOI: 10.3846/jcem.2023.19533
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Opportunities in Application of Business Intelligence in Construction Companies

Abstract: In construction projects, managers make multiple decisions every day. Most of these decisions are relatively unimportant; some of them are critical and could lead to the success or failure of a construction project. To ensure construction companies make effective managerial decisions, decision making requires performing an initial technical and economic analysis, comparing different decision-making solutions, using a planning system, and ensuring project implementation based on the provided plans. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…AI algorithms play a crucial role in dissecting the complexities of demand and supply in the real estate market (Figure 1). By processing vast datasets, these algorithms uncover patterns, identify emerging trends, and contribute to a comprehensive understanding of market dynamics, thereby assisting in strategic decision making [41][42][43]. Real estate investments inherently carry a variety of risks, and AI algorithms surpass in assessing and mitigating these risks [44,45].…”
Section: Ai-driven Algorithms In Real Estate Industry Solution Analysismentioning
confidence: 99%
“…AI algorithms play a crucial role in dissecting the complexities of demand and supply in the real estate market (Figure 1). By processing vast datasets, these algorithms uncover patterns, identify emerging trends, and contribute to a comprehensive understanding of market dynamics, thereby assisting in strategic decision making [41][42][43]. Real estate investments inherently carry a variety of risks, and AI algorithms surpass in assessing and mitigating these risks [44,45].…”
Section: Ai-driven Algorithms In Real Estate Industry Solution Analysismentioning
confidence: 99%
“…The significance of branding and marketing in construction projects Golestanizadeh et al (2023) found that the significance of identified opportunities for utilizing Business Intelligence (BI) in project-based construction companies is above the average level. Moreover, they argue that leveraging BI in such companies allows for capitalizing on these opportunities to enhance project performance.…”
Section: 3mentioning
confidence: 99%
“…Golestanizadeh et al. (2023) found that the significance of identified opportunities for utilizing Business Intelligence (BI) in project-based construction companies is above the average level.…”
Section: Literature Reviewmentioning
confidence: 99%